Analisis Faktor-Faktor yang Mempengaruhi Ketepatan Waktu Penyampaian Laporan Keuangan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (Studi Empiris pada Perusahaan Sektor Industri Dasar dan Kimia) - Indrayenti INDRAYENTI; Cindrawati Ie (Jurnal Akuntansi dan Keuangan, 2016)
This study purposed to test factors which were affecting timeliness offinancial statements in manufacture companies listed in IndonesianStock Exchange. Factors tested in this study is profitability, liquidity, company size,company age, and audit opinions. Samples used in this study are purposive sampling in amount of 20 selected companies by various samples selection criteria. Later, those factors will be tested by logistic regression by significant level of 5%. Result identifies that profitability, liquidity, company size,company age,and audit opinion doesn’t have any effect on timeliness offinancial statements in Indonesian Stock Exchange.